Malleability of Thought: Synergy of Buddhist Ideas and the Treatment of Addiction. - Brower, Matthew C (Health & Social Work, 2026)
This article examines how Buddhist concepts can be integrated into addiction treatment to support social work practice. It highlights key Buddhist ideas such as impermanence (anitya), suffering (dukkha), and the non-static self, which help clients reframe their addictions as changeable rather than fixed identities. Mindfulness-based interventions, including mindfulness-based relapse prevention (MBRP) and acceptance and commitment therapy (ACT), are discussed as evidence-based approaches that incorporate Buddhist meditation techniques to enhance clients’ awareness, psychological flexibility, and relapse prevention. The article emphasizes the importance of social workers embodying mindfulness practices themselves to effectively guide clients in transforming addictive behaviors.